APPLICATION AND FUNCTIONS OF TOPONYMS IN POETIC SPEECH (Scientific journal of the Fergana State University, 2023)
In the article, the stylistic, artistic and aesthetic functions of place names – toponyms specific to Uzbek poetic discourse, as well as the characteristics of their use as a linguopoetic tool, are highlighted on the basis of evidence. In the case of Erkin Vahidov, Abdulla Oripov, Muhammad Yusuf's poetry, toponyms are linguistically based artistic-methodical tools and poetic arts are researched on the basis of lexical-semantic, methodological, linguopoetic analysis methods. It is proved that toponymic units such as choronym, polysonym, commononym, hydronym perform linguopoetic and methodological functions in poetic speech like other onomastic units.